Emotional earthquakes in the landscape of psychosis: an interpretative phenomenology. (7th November 2016) - Hutchins, Jonathan; Rhodes, John; Keville, Saskia
Abstract: Traditionally studies have neglected emotion in psychosis, possibly as a consequence of psychiatry's emphasis on psychotic symptoms rather than individuals' lived experience of emotions before, during and after psychotic episodes. This study sought to investigate how individuals experienced their emotions and delusions in the context of psychosis. A qualitative Interpretative Phenomenological Analysis (IPA) research methodology was used. Semi-structured interviews were conducted with a purposively sampled group of eight participants recruited from a local Early Intervention in Psychosis service. Four themes were generated by the analysis. The first highlighted emotional experiences prior to the onset of psychosis: 'struggling with life distress'. The second highlighted the intense emotional experience within psychotic experiences: 'transformed world and intense emotion'. The third theme highlighted self-critical tendencies in the post-onset phase of psychosis: 'blame and guilt after the breakdown'. The final theme highlighted a mixture of emotions in the post-onset phase: 'confusion, despair and hope'. There were many clinical implications highlighted in the study including the value of normalizing participants' emotional experiences in order to promote engagement in services and of assessing for self-criticism, despair and hope following the psychotic experience, alongside therapeutically addressing the varying levels of emotional experiences before, during and after a psychotic breakdown.